SCIENTOMETRIC HIGHLIGHTS ON SCIENCE AND TECHNOLOGY RELATED REVIEW ARTICLES AFFILIATED TO INDIA - Sagar, Anil; V. L., Kalyane; E. R., Prakasan; R. G., Garg; Kumar, Vijai (Malaysian Journal of Library and Information Science, 2009)
Review Articles are of primary importance as a scholarly output and have become a secondary source in order to access older primary literature. The present study is a quantitative documentation of ‘Review Articles’ published during 2000-2005 in the Science Citation Index (SCI) and having India in the affiliation of authors. SCI considers article having 100 or more synchronous references as ‘review’. Records with ‘Review’ in Document type field are extracted out from the results of the search ‘India’ in the ‘Address word’ field for the indicated publication period, which resulted in a total of 2042 records by 5135 individual authors in over 640 individual journals. Authors from Bhabha Atomic Research Centre, Mumbai, India are in the forefrontm among the most productive review writers. Findings indicated that the average yearly growth rate is 11.04, and that 85.16 per cent of the total Review Articles are written in collaboration. Of these collaborative works, 22.9 percent are written with authors from 78 different countries. The study clearly shows that collaboration of Indian reviewers with people from outside India is significant. Multidisciplinary Sciences; Chemistry in General; General and Internal Medicine; Biochemistry and Molecular Biology; and Pharmacology and Pharmacy are the main fields in which majority of the Review Articles are written. The inter-quartile mean of the number of Synchronous References of the 2042 Review Articles is found as 94.84.